Lossless compression of topology of 3D triangulated irregular networks - Nguyen, Viet Pham; Ung, Each Muy; Krishna, Aneesh; Tham, S. (2016)
With the increase in popularity of using 3-D complex models within applications such as the 3-D Geographic Information System (GIS), an effective compression of 3-D models has become more important, so as to allow faster transmission from server to client. Many techniques have been proposed to compress manifolds. Such techniques are able to achieve impressive compression rates. Unfortunately, techniques capable of dealing with non-manifolds, or high-genus manifolds, are scarce. This paper presents a novel compression technique for high-genus manifolds and non-manifold models. The proposed technique, AComp, is able to produce models compressed by 60% or even more compared to those compressed by GZip.